Production of halogenated indigo by Escherichia coli whole-cell conversion system with novel halogenase derived from Pseudoalteromonas nigrifaciens - Yi, Byongson; Lee, Byung Wook; Yu, Kyungjae; Koh, Hyun Gi; Yang, Yung Hun; Choi, Kwon Young; Kim, Byung Gee; Ahn, Jung Oh; Park, Kyungmoon; Park, See Hyoung (Biotechnology and Bioprocess Engineering, 2024)
Indigo is a commercially significant dye extensively used in the textile industry for dyeing denim and other fabrics. The synthesis of various colored indigo derivatives necessitates the halogenation of the indole ring in indigo. However, the scarcity of halogenating enzymes, especially those with high positional specificity and commercial availability, limits the biological synthesis of various halogenated indigos. This study presents the discovery of a novel halogenase from Pseudoalteromonas nigrifaciens that is similar to sttH from Streptomyces toxytricini, an enzyme that specifically halogenates the 6th carbon of the indole in indigo. The cloned halogenase gene was validated for halogenation activity and regioselectivity using a recombinant Escherichia coli whole-cell conversion system. The addition of either NaCl or NaBr resulted in the production of 6-chloro indigo or 6-bromo indigo, respectively. Notably, 6-chloro indigo displayed a red coloration, while 6-bromo indigo appeared blue. To optimize the whole-cell conversion system, we evaluated the conversion rate of halogenated indigo production in response to varying concentrations of tryptophan and E. coli cells. The maximum conversion rate (32%) was achieved using 30 mM tryptophan and an E. coli cell density corresponding to an OD50 reading. In conclusion, we have designed a recombinant E. coli whole-cell conversion system capable of producing 6-halogenated indigo by introducing a novel sttH-like halogenase from P. nigrifaciens. This system holds promise for the production of various indigo derivatives.
Keywords: Conversion rates; Conversion systems; E.coli cells; Indigo; Indigo derivatives; Indole; Pseudoalteromona nigrifaciens; Pseudoalteromonas; Stth; Whole-cell conversion; Halogenation; Indigo; Indole; Pseudoalteromonas nigrifaciens; sttH